Response of Tree Seedlings to a Combined Treatment of Particulate Matter, Ground-Level Ozone, and Carbon Dioxide: Primary Effects - Valentinas Černiauskas; Iveta Varnagirytė-Kabašinskienė; Ieva Čėsnienė; Emilis Armoška; Valda Araminienė (Plants)
Trees growing in urban areas face increasing stress from atmospheric pollutants, with limited attention given to the early responses of young seedlings. This study aimed to address the knowledge gap regarding the effects of simulated pollutant exposure, specifically particulate matter (PM), elevated ozone (O3), and carbon dioxide (CO2) concentrations, on young seedlings of five tree species: Scots pine (Pinus sylvestris L.); Norway spruce (Picea abies (L.) H.Karst.); silver birch (Betula pendula Roth); small-leaved lime (Tilia cordata Mill.); and Norway maple (Acer platanoides L.). The main objectives of this paper were to evaluate the seedling stem growth response and the biochemical response of seedling foliage to pollutant exposure. Four treatments were performed on two- to three-year-old seedlings of the selected tree species: with PM (0.4 g per seedling) under combined O3 = 180 ppb + CO2 = 650 ppm; without PM under combined O3 = 180 ppb + CO2 = 650 ppm; with PM (0.4 g per seedling) under combined O3 < 40–45 ppb + CO2 < 400 ppm; and without PM under combined O3 < 40–45 ppb + CO2 < 400 ppm. Scots pine and Norway maple showed no changes in growth (stem height and diameter) and biochemical parameters (photosynthetic pigments, total polyphenol content (TPC), total flavonoids content (TFC), and total soluble sugars (TSS)), indicating a neutral response to the combined PM, O3, and CO2 treatment. The chlorophyll response to PM alone and in combination with elevated O3 and CO2 exposure varied, with silver birch increasing, Norway maple—neutral to increasing, Scots pine—neutral to decreasing, and Norway spruce and small-leaved lime—decreasing. The TPC indicated stress responses in Scots pine, small-leaved lime, and Norway maple under increased combined O3 and CO2 and in Norway spruce under single PM treatment. Hence, Scots pine and Norway maple seedlings showed greater resistance to increased PM under combined O3 and CO2 with minimal change in growth, while silver birch seedlings showed adaptation potential with increasing chlorophyll under simulated pollutant stress.